Strategies of Entrepreneurial Software Developing Companies (ESDCS) in Malaysia and Bangladesh: A Comparative Analysis for Sustainable Development of ESDCS in Bangladesh - Nazrul Islam,; Barbara Igel,; Muhammad Z. Mamun, (Asian Academy of Management Journal, 1999)
The increasing pace of changes in software developing industry (SDI) is forcing Entrepreneurial Software Developing Companies (ESDCs) to make their strategies explicit. This has given rise to various successful strategies and management practices of the ESDCs over the years ( Hill and Jones, 1995). For many developing countries, however, the underlying issues resolve around finding the most viable development strategy of technology advancement. These countries seem to have inadequate technological capability and lack of core competency to determine the plan most relevant with their development goals that will maximize utility of their abundant human resources effectively and to develop capability and core competency ESDCs have to apply appropriate strategies at all levels. ESDCs are the most fragile firms. The nature of their vulnerability is due to the rapid rate of technological change, market volantility and uncertainty, competition, employee technical skills, resource constraints, and the technology-based entrepreneur founding team (Slatter,1992; Riggs, 1995 ; Bruch, 1997; Newell and Saxberg1985, Shanklin 1985, Rogers, 1995). Due to its fragile nature, the strategic consideration becomes even more important. ESDCs are also oriented to business services along with innovation (Swierezek, 1992). As such, they are important for a nation's economy and development. Many of them are innovators and developers of tomorrow's industrial technology on which the respective countries future economic progress depend (Glinow and Mohrman, 1990) Hence to develop ESDCs, business support services are also very much required. This is a case for both Bangladesh and Malaysia